Flexible Multi-Beam Light-Sheet Fluorescence Microscope for Live Imaging Without Striping Artifacts - Sancataldo, Giuseppe; Gavryusev, Vladislav; de Vito, Giuseppe; Turrini, Lapo; Locatelli, Massimiliano; Fornetto, Chiara; Tiso, Natascia; Vanzi, Francesco; Silvestri, Ludovico; Pavone, Francesco Saverio (Frontiers in Neuroanatomy, 2019)
The development of light-sheet fluorescence microscopy (LSFM) has greatly expanded the experimental capabilities in many biological and biomedical research fields, enabling for example live studies of murine and zebrafish neural activity or of cell growth and division. The key feature of the method is the selective illumination of a sample single plane, providing an intrinsic optical sectioning and allowing direct 2D image recording. On the other hand, this excitation scheme is more affected by absorption or scattering artefacts in comparison to point scanning methods, leading to un-even illumination. We present here an easily implementable method, based on acousto-optical deflectors (AOD), to overcome this obstacle. We report the advantages provided by flexible and fast AODs in generating simultaneous angled multiple beams from a single laser beam and in fast light sheet pivoting and we demonstrate the suppression of illumination artefacts.